Descriptions of seed sources and collections for provenances of Pinus caribaea - Greaves, A (Commenwealth Forestry Institute, University of Oxford, 1978)
The history of the use of Pinus caribaea Morelet as an exotic plantation species is given by Lamb (1973). The first introductions took place as early as 1929, but it was not until 1960 that a general interest in the species by many tropical countries developed. In that year the FAO Seminar on Tropical Pines held in Mexico (I.N.I.F., 1962) stimulated an awareness of the potentially valuable role that many tropical pines might play in afforestation schemes. One consequence of this was that P. caribaea began to receive close attention. The results from the limited number of exotic trials in existence were promising. Moreover most of the natural populations of this species are found on degraded and infertile soils within the humid tropical lowlands, the kind of sites that many countries are anxious to bring into useful productivity...